Analisis Pengaruh Faktor-Faktor Yang Mempengaruhi Retensi Karyawan Pada Kantor Energi Dan Sumber Daya Manusia Provinsi Sumatera Utara - Tesar, Wahyu (Universitas Harapan Medan, 2025)
This study aims to determine the effect of competence, co-workers and communication on employee retention at the Office of Energy and Human Resources of North Sumatra Province either partially or simultaneously. The population in this study amounted to 172 people, and using the Slovin formula obtained a sample of 63 people. The analysis technique used is multiple linear regression. The results showed that the style of compensation had a positive and significant effect on employee retention at the Office of Energy and Human Resources of North Sumatra Province. Colleagues have a positive and significant effect on employee retention at the Office of Energy and Human Resources of North Sumatra Province. Communication has no effect on employee retention at the North Sumatra Province Energy and Human Resources Office. Compensation, co-workers and communication have a positive and significant effect on employee retention at the Office of Energy and Human Resources of North Sumatra Province.